Channel flow of a compressible fluid (Fluid mechanics films., 1988)
Schlieren flow visualization and simultaneous display of the pressure distribution along a channel of varying area demonstrate the phenomena of choking, blocking and starting. Shows supersonic flow, Mach waves, normal shock waves and supersonic compression.